Prospects and Challenges of Mushroom Cultivation in Godavari Municipality, Nepal - Khadka, Gopal (GS Spark: Journal of Applied Academic Discourse, 2023)
Mushroom cultivation is a viable option for farmers in Nepal due to the availability of raw materials and a favorable environment. Oyster mushrooms are the preferred variety among Nepalese farmers, and they cultivate them throughout the year. This article focuses on the prospects and challenges of mushroom cultivation in Godavari Municipality, based on primary and secondary sources of data. The primary data were collected through interviews with 20 farmers involved in mushroom farming. The study found that mushroom cultivation has high prospects due to its rich source of nutrition, source of income, and medicinal use. Additionally, mushrooms are a ready-to-eat food in various forms, such as fried, crispy, noodles, and more. They can also be used to make delicious pickles, chutney, cake, tea, and biscuits. Furthermore, mushrooms can be processed into powdered form, capsule form, canned products, and mushroom-enriched cosmetics such as soap, toothpaste, cream, oil, etc. By diversifying agricultural production and generating significant employment opportunities, mushroom farming can become a lifeline for rural and semi-urban areas. However, the study also found that mushroom cultivation faces challenges such as the high cost of raw materials, lack of labor, and an imperfect market. To mitigate these challenges, the local government must formulate effective policies to promote mushroom farming in the Nepalese context. Mushroom cultivation has significant prospects in Godavari Municipality, Nepal, due to its nutritional value, medicinal uses, and various forms of consumption. However, there are also challenges that farmers face, such as the high cost of raw materials and lack of labor. By implementing effective policies, the local government can help to mitigate these challenges and promote mushroom farming as a viable and profitable crop for Nepalese farmers.